CONSIDERING THE EFFECT OF BUILDING FORM ON ENERGY EFFICIENCY - Gulmira Shungaraeva Berdishukirovna; Mirolimov Mirrahim Mirmahmudovich (American Journals Publishing, 2023)
The influence of building plan configurations in relation to their spatial characteristics on their energy consumption is considered. The article substantiates the relevance of the research of space-planning solutions of building forms, taking into account energy efficiency. As the object of research, the authors selected the most common three-dimensional configurations of building forms, taking into account energy efficiency. Examples of the analysis of the main space-planning parameters of the building and the prerequisites for their influence on its heat loss are considered with the provided graphic materials that allow you to find out the dependence of the change in the area of enclosing structures on the change in the floor area. This comparison is carried out in order to determine an energy-efficient and rationally arranged space-planning solution, taking into account the principles of energy saving for the construction of buildings.
Keywords: Energy efficiency, volume-planning solution, heat loss, compactness coefficient, power consumption.